Pengaruh Model Teams Games Tournament (TGT) Berbantuan Permainan Engklek Pada Pendidikan Pancasila Untuk Meningkatkan Karakter Berkebhinekaan Global Siswa Kelas IV - Safitri, Kadek Devi; Pancaria, I Nyoman; Ardiawan, I ketut Ngurah (IJPSE Indonesian Journal of Primary Science Education, 2025)
This study aims to analyze the extent to which the Team Games Tournament (TGT) model combined with the traditional game Engklek influences the formation of global diversity character for fourth grade elementary school students in Gugus 6 Sawan District by choosing Pancasila Education subjects. The method used in this research is quasiexperiment with post-test only control group design. The study population consisted of fourth grade students at SDN Gugus 6 Sawan District. The experimental group consisted of 27 students from class IV SDN 4 Sangsit and the control group consisted of 19 students from class IV SDN 7 Sangsit. Data collection techniques include interviews, observation, documentation, and questionnaires, while data analysis techniques include content validity tests, descriptive analysis, normality, homogeneity, paired sample t-test, and effect size. The t-test results showed a Sig. (2-tailed) 0.000 <0.05, with an average learning attitude of the experimental group of 70.93 and the control group (70.93>64.79). This means that the Team Games Tournament (TGT) model assisted by the Engklek game has a positive effect on the global diversity character of fourth grade students of SDN Gugus 6 Sawan District in the 2024/2025 academic year.